A 58-Year-Old Male with Nasopharyngeal Papillary Adenocarcinoma: A Case Report - Dewi Susilowati; Dwi Antono; Nur Iman Nugroho (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal Papillary Adenocarcinoma (NPAC) is a very rare type of nasopharyngeal cancer. NPAC was distinguished from common nasopharyngeal cancer due to its specific histological type. Case Report: We reported a case of a 58-year-old male patient with complaints of headache, mass in the nasopharynx, and lumps on both sides of the neck. Based on his history of illness, physical examination, imaging, and histopathology, we concluded that he was diagnosed with Nasopharyngeal Papillary Adenocarcinoma (NPAC). Six cycles of paclitaxel-cisplatin chemotherapy regimen were planned for the patient. The patient was currently undergoing his fifth cycle of chemotherapy and showed a good response. Conclusion: The chemotherapy management of this patient was given according to the general management of nasopharyngeal carcinoma to increase the good response of the patient.